2022
DOI: 10.3389/fpls.2022.908218
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Methylation of 35S rDNA in Allopolyploids Anemone multifida (2n = 4x = 32, BBDD) and Anemone baldensis (2n = 6x = 48, AABBDD) and Their Parental Species Show Evidence of Nucleolar Dominance

Abstract: Transcriptional silencing of 35S rDNA loci inherited from one parental species is occurring relatively frequently in allopolyploids. However, molecular mechanisms by which it is selected for transcriptional silencing remain unclear. We applied NGS, silver staining and bisulfite sequencing to study the structure, expression and methylation landscape of 35S rDNA in two allopolyploids of common origin, allotetraploid Anemone multifida (2n = 4x = 32, genome composition BBDD) and allohexaploid A. baldensis (2n = 6x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
(185 reference statements)
0
2
0
Order By: Relevance
“…In interspecific or intergeneric hybridizations, rRNA genes from both parents are actively transcribed (Borowska‐Zuchowska et al., 2021; Matyasek et al., 2016; Sochorova et al., 2017). However, in other cases, only rRNA genes inherited from one parent are actively transcribed, while those from the other progenitors are transcriptionally silenced (Borowska‐Zuchowska et al., 2020; Chen & Pikaard, 1997b; Guo & Han, 2014; Mirzaghaderi et al., 2017; Mlinarec et al., 2022; Sochorova et al., 2017; Xiao et al., 2016). Nucleolar dominance (ND) refers to the epigenetic phenomenon where rRNA genes from only one parent are transcriptionally active (Lawrence & Pikaard, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In interspecific or intergeneric hybridizations, rRNA genes from both parents are actively transcribed (Borowska‐Zuchowska et al., 2021; Matyasek et al., 2016; Sochorova et al., 2017). However, in other cases, only rRNA genes inherited from one parent are actively transcribed, while those from the other progenitors are transcriptionally silenced (Borowska‐Zuchowska et al., 2020; Chen & Pikaard, 1997b; Guo & Han, 2014; Mirzaghaderi et al., 2017; Mlinarec et al., 2022; Sochorova et al., 2017; Xiao et al., 2016). Nucleolar dominance (ND) refers to the epigenetic phenomenon where rRNA genes from only one parent are transcriptionally active (Lawrence & Pikaard, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in antipatharians from shallow-water black corals, it was first confirmed that ITS rRNA regions can be used as markers at both the species and population levels [ 25 ]. The utilization of the ITS1 region as a marker for the identification of nematode species or populations has great potential in nematology [ 26 ]. Molecular techniques based on the restriction digestion of the ITS1 region were used to examine the species or populations of geographically dispersed nematodes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%